Harnessing the microbiome to control plant parasitic weeds. (June 2019) - Masteling, Raul; Lombard, Lorenzo; de Boer, Wietse; Raaijmakers, Jos M; Dini-Andreote, Francisco
Highlights: Plant microbiomes have an unexplored potential to control root parasitic weeds. Understanding the mechanisms by which microbes can control parasitic weeds is largely elusive. Members of the root microbiome can interfere with host-parasite chemical communication. Direct and indirect modes of action can work synergistically in microbe-mediated weed control. Abstract : Microbiomes can significantly expand the genomic potential of plants, contributing to nutrient acquisition, plant growth promotion and tolerance to (a)biotic stresses. Among biotic stressors, root parasitic weeds (RPWs), mainly of the genera Orobanche, Phelipanche and Striga, are major yield-limiting factors of a wide range of staple crops, particularly in developing countries. Here, we provide a conceptual synthesis of putative mechanisms by which soil and plant microbiomes could be harnessed to control RPWs. These mechanisms are partitioned in direct and indirect modes of action and discussed in the context of past and present studies on microbe-mediated suppression of RPWs. Specific emphasis is given to the large but yet unexplored potential of root-associated microorganisms to interfere with the chemical signalling cascade between the host plant and the RPWs. We further provide concepts and ideas for future research directions and prospective designs of novel control strategies.